An Analysis of a Minimal Vectorlike Extension of the Standard Model - V. Beylin; M. Bezuglov; V. Kuksa; N. Volchanskiy (Advances in High Energy Physics)
We analyze an extension of the Standard Model with an additional SU(2) hypercolor gauge group keeping the Higgs boson as a fundamental field. Vectorlike interactions of new hyperquarks with the intermediate vector bosons are explicitly constructed. We also consider pseudo-Nambu–Goldstone bosons caused by the symmetry breaking SU(4)→Sp(4). A specific global symmetry of the model with zero hypercharge of the hyperquark doublets ensures the stability of a neutral pseudoscalar field. Some possible manifestations of the lightest states at colliders are also examined.